"Now I feel much better than in my previous life": Narratives of occupational transitions in young transgender adults. Issue 2 (3rd April 2019) - Schneider, Jens; Page, Julie; van Nes, Fenna
ABSTRACT: Research indicates that the life courses of transgender people are accompanied by occupational transitions, defined as specific moments in life at which occupations change in favour of alternative occupations due to reactions to life events. This study used a narrative approach to gain a better understanding of the occupational transitions experienced by four German transgender adults during the development of their gender identity from early childhood to early adulthood. The participants were aged between 19 and 25. Data were collected through narrative interviews and resulted in four stories developed using narrative analysis. The participants underwent a variety of occupational transitions. These started in their earliest childhood, when they acted like members of their felt gender for the first time. The occupations performed by the participants during the development of their transgender identity changed to specific occupations related to gender transition and finally resulted in the occupational life of their felt gender. The stories give an insight into numerous issues related to occupational performance and occupational transitions in childhood, puberty and early adulthood. Sometimes the participants experienced occupational losses. At other times, their occupational identities were positively affected by their gender transitions, with the result that they were able to live their lives more in keeping with their gender identities. The researchers concluded that studies with transgender people will contribute to a better understanding of the interaction of gender and the performance of occupations.